2004
DOI: 10.1128/jb.186.23.7980-7987.2004
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Region Recognized by the Nitric Oxide-Responsive Transcriptional Activator NorR Is Conserved in β- and γ-Proteobacteria

Abstract: The 54 -dependent regulator NorR activates transcription of target genes in response to nitric oxide (NO) or NO-generating agents. In Ralstonia eutropha H16, NorR activates transcription of the dicistronic norAB operon that encodes NorA, a protein of unknown function, and NorB, a nitric oxide reductase. A constitutively activating NorR derivative (NorR), in which the N-terminal signaling domain was replaced by MalE, specifically bound to the norAB upstream region as revealed by gel retardation analysis. Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…However, two putative consensus sequences for a NorR-binding box [GT-(N 7 )-AC] were found upstream of the rd-roo coding region. According to genome database analyses, this inverted repeat is found in several bacteria upstream of gene loci encoding proteins involved in nitric oxide metabolism (6), which is in agreement with our results regarding the involvement of ROO in NO detoxification in D. gigas.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, two putative consensus sequences for a NorR-binding box [GT-(N 7 )-AC] were found upstream of the rd-roo coding region. According to genome database analyses, this inverted repeat is found in several bacteria upstream of gene loci encoding proteins involved in nitric oxide metabolism (6), which is in agreement with our results regarding the involvement of ROO in NO detoxification in D. gigas.…”
Section: Discussionsupporting
confidence: 81%
“…Total RNA was treated with DNaseI RNase-free (Roche), and Transcriptor Reverse Transcriptase (Roche) was used to synthesize cDNA with the random primer p(dN) 6 , according to the manufacturer's instructions. To rule out the presence of DNA in the RNA preparation, a control reaction was performed without the RT (no-RT control).…”
Section: Rna Isolation and Real-time Reverse Transcription-pcr (Rt-pcmentioning
confidence: 99%
“…NorR is a r 54 -dependent transcriptional activator that regulates expression of the NO reductase operons, norVW in E. coli and norAB in R. eutropha [21,22]. NorR binds to three tandem operator regions, inverted repeats with degenerate consensus GT-(N 7 )-AC, which are localized upstream of the r 54 promoter site [23]. By applying the motif detection procedure to the hcp promoter regions from four Vibrionales genomes, we identified two tandem palindromic sites with consensus GATGT-(N 7 )-ACATC (Figure S4).…”
Section: Norr Regulonmentioning
confidence: 99%
“…Three tandem upstream activator sites with the core consensus GT-(N 7 )-AC were identified as NorR-binding sites observed in both promoter regions. Analysis of the adjacent regions of additional norR orthologs in bacterial genomes revealed similar tandem NorRbinding sites upstream of the norA and norB genes in Ralstonia species, norVW in Salmonella species, hmp in Vibrio cholerae and Pseudomonas aeruginosa, and hcp in V. vulnificus [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, genomic analysis revealed that NorR orthologs are widely distributed among beta-and gammaproteobacteria (22). Like all proteins of the 54 -dependent NtrC/NifA superfamily (25), NorR shows a typical modular structure, including an N-terminal domain (NTD), a central AAAϩ domain, and a helix-turn-helix domain for DNA binding (3,21). In a recent study, it was shown that the NTD of E. coli NorR harbors a mono-iron center that is able to bind NO as a ferrous nitrosyl (10).…”
mentioning
confidence: 99%